2009
DOI: 10.1111/j.1600-0714.2008.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of Annexin A1 correlates with pathologic differentiation grade in oral squamous cell carcinoma

Abstract: Previously, we established an in vitro cellular carcinogenesis model of oral squamous cell carcinoma (OSCC), including the human immortalized oral epithelia cells (HIOECs) and its derived cancerous HB96 cells. In this study, comparative proteomic analysis identified that Annexin A1 was one of the significantly down-regulated genes in the cancerous HB96 cells. To investigate Annexin A1 down-regulation and its potential usefulness as a molecular marker in OSCC, we further screened Annexin A1 expressions with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Zhu et al (24,25) and Zhang et al (26) reported that ANXA1 expression is significantly correlated with the pathological differentiation grade in OSCC patients. A lower ANXA1 expression in OSCC tissues correlates to a poorer pathologic differentiation grade (25,26). ANXA1 mRNA is downregulated in peripheral blood from OSCC patients compared with that in negative control individuals (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al (24,25) and Zhang et al (26) reported that ANXA1 expression is significantly correlated with the pathological differentiation grade in OSCC patients. A lower ANXA1 expression in OSCC tissues correlates to a poorer pathologic differentiation grade (25,26). ANXA1 mRNA is downregulated in peripheral blood from OSCC patients compared with that in negative control individuals (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, ANXA1 acts as a tumor suppressor by reducing cell proliferation and attenuating the metastatic potential in breast cancer (23). Certain clinical studies revealed that ANXA1 is downregulated in OSCC patients, and its expression is associated with the pathologic differentiation grade in OSCC patients (18,(24)(25)(26). However, the direct function of ANXA1 in OSCC progression has remained to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of ANXA1 has been cor related with the development of hepatocellular carcinoma, colorectal cancer, lung cancer, pancreatic cancer, melanoma, skin cancer and endometrial carcinoma (21)(22)(23)(24)(25)(26)(27). Furthermore, its downregulation, as well as the translocation of ANXA1, has been shown to be a positive indicator for the development, progression and metastasis of prostate cancer, esophageal cancer, oral carcinoma, cervical cancer, intestinal-type sinonasal adenocarcinoma and NPC (17)(18)(19)28,29). Yu et al (20) reported that the expression of ANXA1 was downregulated in the adriamycin-resistant cell line (pumc-91/ADM) compared with its parental cell line (pumc-91).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of ANXA1 in the malignant tumor has emerged as a research focus in oncology. Accumulating evidence has indicated that ANXA1 dysregulation is associated with the occurrence, development, invasion, metastasis and drug resistance of cancers (17)(18)(19)(20). The research evidence indicated that ANXA1 may specifically function as either a tumor suppressor or an oncogene candidate for certain cancers depending on the particular type of tumor cells/tissues (9).…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC), the sixth most common cancer, continues to be the most prevalent cancer related to the consumption of tobacco and alcohol [1], affecting approximately 500,000 patients worldwide each year [2,3]. More than 300,000 new cases are reported in America every year, and approximately 9,000 patients die each year of the disease.…”
Section: Introductionmentioning
confidence: 99%